Evolution of lbx spinal cord expression and function. Issue 5 (19th August 2021) - Juárez‐Morales, José Luis; Weierud, Frida; England, Samantha J.; Demby, Celia; Santos, Nicole; Grieb, Ginny; Mazan, Sylvie; Lewis, Katharine E.
Abstract: Ladybird homeobox (Lbx) transcription factors have crucial functions in muscle and nervous system development in many animals. Amniotes have two Lbx genes, but only Lbx1 is expressed in spinal cord. In contrast, teleosts have three lbx genes and we show here that zebrafish lbx1a, lbx1b, and lbx2 are expressed by distinct spinal cell types, and that lbx1a is expressed in dI4, dI5, and dI6 interneurons, as in amniotes. Our data examining lbx expression in Scyliorhinus canicula and Xenopus tropicalis suggest that the spinal interneuron expression of zebrafish lbx1a is ancestral, whereas lbx1b has acquired a new expression pattern in spinal cord progenitor cells. lbx2 spinal expression was probably acquired in the ray‐finned lineage, as this gene is not expressed in the spinal cords of either amniotes or S. canicula . We also show that the spinal function of zebrafish lbx1a is conserved with mouse Lbx1. In zebrafish lbx1a mutants, there is a reduction in the number of inhibitory spinal interneurons and an increase in the number of excitatory spinal interneurons, similar to mouse Lbx1 mutants. Interestingly, the number of inhibitory spinal interneurons is also reduced in lbx1b mutants, although in this case the number of excitatory interneurons is not increased. lbx1a;lbx1b double mutants have a similar spinal interneuron phenotype to lbx1a single mutants. Taken together these data suggest that lbx1b and lbx1a may be required in succession for correct specification of dI4 and dI6 spinal interneurons, although only lbx1a is required for suppression of excitatory fates in these cells. Abstract : Research Highlights: lbx1 spinal expression and function is conserved in vertebrates. In contrast, zebrafish lbx1b and lbx2 have novel spinal expression patterns that probably evolved in the ray‐finned vertebrate lineage ( lbx2 ) or teleosts ( lbx1b ).